A review of research on the relationship between physical activity and creativity within the context of school physical education - Khorkova, Maryna; Bojkowski, Łukasz; Bronikowski, Michał (Physical education, sport and olympism from a pedagogical perspective, 2023)
One of the current areas of theoretical considerations and scientific research in the field of physical culture sciences is the development of creativity of students (at various levels of education) and their creative abilities, which is supposed to take place through the use of various educational forms – plays, games, activities or tasks that help develop specific dispositional characteristics of a young person. In these studies, very often (taking into account the review of the world literature), great importance is attached to adapted physical activity, which, thanks to its diversity and the possibility of wide application, can affect not only the aspects of motor and movement skills of children, but also – by stimulating selected structures brain – for the development of various cognitive functions. At the same time, the importance of exercises involving strictly creativity training in the process of modern physical education is described, where the use of selected didactic methods is to contribute, among others, to the increase of students' interest in activities based on physical involvement.An example of such a method are tasks using EduBalls and mini-EduBalls, which allow students to combine physical activity (gross and fine movement skills and basic motor skills) with their education (in the area of language, graphomotor and mathematical skills) or stimulation of cognitive structures, which was confirmed in numerous studies.